Dietary fiber tragacanth gum based hydrogels for use in drug delivery applications. (January 2020) - Singh, Baljit; Sharma, Kanika; Rajneesh,; Dutt, S.
Abstract: There is no doubt that fibers, in particular viscous dietary fibers, have positive effects on the human health, both in the prevention and in the treatment of chronic diseases. The present work explore the potential of dietary fiber tragacanth gum (TG) for developing hydrogels as drug carrier for anti-cancer drug 'methotrexate' to improve its pharmacokinetic deficiency due to nonspecific distribution and enhancing. Polymer matrix was characterized by SEMs, FTIR and XRD techniques. Release profile of drug was determined along with evaluation of some properties like blood compatibility, mucoadhesion and mechanical strength. The release profile occurred with non-Fickian diffusion mechanism and was best fitted in the Higuchi kinetic model. The polymer matrix was non-thrombogenic, haemo-compatible and mucoadhesive in nature. The hydrogels adhered to intestinal mucosa with 14.3 ± 4.5 mN force during mucoadhesion test.